Holographic technologies (selection of papers from the HOLOEXRO 2019 conference) : Limiting the number of quantisation levels of a harmonic lens as a method for improving the quality of the generated image. (31st July 2020) - Skidanov, R V; Ganchevskaya, S V; Vasil'ev, V S; Kazanskiy, N L
Abstract: The characteristics (modulation transfer functions) of harmonic lenses made by direct laser patterning of resist are experimentally studied. The influence of technological errors in the manufacture of lenses on the formation of the point spread function is modelled for harmonic lenses with 32 and 256 quantisation levels. Direct laser writing is used to produce lenses with these numbers of levels. It is experimentally shown that the modulation transfer function of the harmonic lens with 32 quantisation levels is significantly greater at high spatial frequencies (50 mm -1 ).